Spectroscopic and Substitution Kinetic Studies of Hexacyanoferrate(II) Complexes byEDTA Catalysed with Mercury(II) - K. S. Siddiqi; Aftab Aslam Parwaz Khan; Ayaz Mohd; Shaista Bano (E-Journal of Chemistry)
Kinetics and mechanism of substitution of cyanide ion in hexacyanoferrate(II) by EDTA catalysed by mercury(II) has been studied spectrophotometrically at 365 nm in potassium hydrogen phthalate buffer of pH = 5.0 and ionic strength, I = 0.1 M, maintained by (KNO3) at 25 °C. Effect of the pH and concentration of the EDTA, [Fe(CN)4-6] on the rate of reaction has been studied. The kinetics and mechanism of the reaction has been shown through dissociative mechanism. The mechanism of ligand substitution in the complex together with the kinetic data has been shown. The catalytic activity of mercury(II) has also been studied as a function of its concentration. The maximum reaction product was detected at pH = 5 after which a decline in absorption occurs followed by precipitation. It is an inexpensive method to identify and remove the cyanide ion in solution even in very low concentration of the order of 10-4 M.